Digital Leadership and Organizational Innovation: The Key to Successful Business Transformation of MSMEs - Prameswari, Nadia; Nugroho, Dimas Arya (Jurnal Ilmiah Manajemen, Ekonomi dan Bisnis, 2025)
Digital transformation is a prerequisite for micro, small, and medium-sized enterprises (MSMEs) to maintain competitiveness in the digital economy; however, it remains constrained by low levels of digital readiness and weak leadership. This study examines the effect of digital leadership on MSME business transformation, with organizational innovation serving as a mediating variable. Using a quantitative approach, an explanatory survey was conducted among 230 MSME owners and managers in the service and trade sectors across major Indonesian cities, and the data were analyzed using PLS-SEM. The results indicate that digital leadership has a significant effect on both organizational innovation and business transformation, while organizational innovation partially mediates this relationship. An R² value of 0.598 underscores the critical role of leaders’ capabilities in building a digital vision, fostering collaboration, and cultivating an innovative mindset as key drivers of MSME transformation. The novelty of this study lies in testing an integrative model of digital leadership, organizational innovation, and business transformation within the Indonesian MSME context. Practically, strengthening digital leadership and an innovation-oriented culture emerges as a key strategy for enhancing MSME sustainability and competitiveness.